Quality of architectural education at the Faculty of Architecture of the University of Ljubljana - Fikfak, Alenka (Journal of Architecture and Urbanism, 2013)
The paper presents a study on the quality of architectural education at the Faculty of Architecture (FA) of the University of Ljubljana (UL) and the changes as a result of adopting the new rules, criteria and evaluation systems. In order to improve the quality of education at FA, we look at the indicators related to the data on student learning outcomes and the education as a whole. The formal data and the comparison of performance (quality) indicators between 2006 and 2012 are shown. Additionally, the basic scope of the Long-cycle Master’s Study Programme in Architecture (MSPA) is presented in terms of content and mobility. The focus of architectural education at the UL FA, which includes practical, artistic and research work, and simulates work in the architectural studio, is on Design Studio course, which is directly complemented by the Architectural Workshop course. The work that includes both the individual approach and team work promotes connections among foreign and Slovenian students. Four cases in point are presented, confirming the significance of creative work within the courses of Design Studio, Architectural Workshop and Master Thesis.